Impact of electron–phonon coupling on electron transport through T-shaped arrangements of quantum dots in the Kondo regime - Patryk Florków; Stanisław Lipiński (Beilstein Journal of Nanotechnology, 2021)
We calculate the conductance through strongly correlated T-shaped molecular or quantum dot systems under the influence of phonons. The system is modelled by the extended Anderson–Holstein Hamiltonian. The finite-U mean-field slave boson approach is used to study many-body effects. Phonons influence both interference and correlations. Depending on the dot unperturbed energy and the strength of electron–phonon interaction, the system is occupied by a different number of electrons that effectively interact with each other repulsively or attractively. This leads, together with the interference effects, to different spin or charge Fano–Kondo effects.